Efektivitas Penegakan Hukum Terhadap Kasus Perdagangan Orang di Indonesia: Studi Kasus Implementasi UU Nomor 21 Tahun 2007 - Pupu Sriwulan Sumaya (AWATARA Publisher, 2024)
This study aims to evaluate the effectiveness of law enforcement against human trafficking cases in Indonesia, focusing on the implementation of Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking (UU PTPPO). Using a qualitative approach through case studies, data were collected from interviews with law enforcement officers, victims of human trafficking, and analysis of legal documents. The results of the study indicate that the effectiveness of the PTPPO Law is hampered by limited resources, lack of training for law enforcement officers, and poor coordination between government agencies and non-governmental organizations. Protection for victims is also suboptimal, with difficulty in accessing rehabilitation and support services. The implications of these findings emphasize the need for reforms in resource allocation, training, and improved coordination. This study recommends that the government increase efforts in training law enforcement officers, improve coordination between agencies, and increase public awareness of human trafficking. Further research is expected to explore the role of technology and international comparative studies in handling human trafficking cases.